Comparison of carvedilol and propranolol for secondary prophylaxis of variceal bleed in cirrhotic patients (Journal of Fatima Jinnah Medical University, 2019)
Background: Portal hypertension is predominant sequelae of liver cirrhosis. Carvedilol and propranolol are used to decrease portal pressure which in turn prevents reoccurrence of bleeding episodes in cirrhotic patients diagnosed and treated for upper gastrointestinal bleeding. Only scarce data is available regarding effectiveness of carvedilol and propranolol as prophylaxis. The aim of this study was to compare the effectiveness of carvedilol and propranolol to prevent reoccurrence of bleeding in cirrhotic patients.Patients and Methods: This quasi experimental study was conducted at the Department of Gastroenterology, Shaikh Zayed Hospital, Lahore, Pakistan from November 2016 to October 2017. Patients suffering from chronic liver disease and had first experience of bleed due to esophageal varices identified and treated on the upper gastrointestinal (GI) endoscopy were included in the study. Demography and Child-Turcotte-Pugh (CTP) class were recorded. In order to prevent reoccurrence of bleeding, these patients were randomly allocated prophylaxis treatment groups comprising 75 patients each; Group A (carvedilol 6.25 mg BD) and Group B (propranolol 20mg TDS) for 6 months. Assessment for bleeding episode (if any) and decrease in hemodynamical parameters like pulse rate (PR), mean arterial pressure (MAP) and portal vein flow (PVF) were assessed after 3 and six months intervals. Drug A or B was considered effective if there was no clinical evidence of re-bleed (melena/hematemesis and drop in hemoglobin levels) and decrease in hemodynamical parameters were observed. Data was entered and analyzed using SPSS version 20.0.Results: Out of 75 patients in each group, 45 (60%) were male in group A and 48 (64%) were male in group B. There was no significant difference in terms of gender, age and CTP class in both groups. Recurrence of upper GI bleeding was seen in 15 (25.3%) patients in group A as compared to 32 (42.66%) in group B (p < 0.05). Significant reduction in mean arterial pressure (MAP), heart rate and portal vein flow (PVF) was observed in group A at both 3 and 6 months (p-value< 0.05).Conclusion: Carvedilol when compared to propranolol is better in all parameters measured in this study to reduce portal pressure and decrease bleeding episodes.
Keywords: Variceal bleed; propranolol; carvedilol; MAP; PVF